Micropropagation and analysis of somaclonal variation in “My Da” strawberry ( Fragaria ananassa Duch.) using rapd marker - Trinh, Ngoc Ai; Nghi, Khac Nhu (Academia Journal of Biology, 2025)
In vitro propagation of strawberry presents many challenges that must be addressed to enhance survival rates during ex vitro acclimation and to ensure the production of high-quality seedlings. This study aimed to develop an optimized protocol for the disinfection, multiplication, rooting, and acclimatization of “My Da” cultivar. Results showed that treating runner segments of “My Da” cultivar with 1% NaClO was effective. For multiplication, Murashige and Skoog (MS) medium supplemented with 0.5 mg. L-1 BAP with 0.3 mg. L-1 kinetin for “My Da” yielded the highest shoot proliferation, leaf count, and plant height. Rooting was most effective on half-strength MS medium supplemented with 0.3 mg. L-1 BAP provided optimal rooting results. In the acclimatization stage, seedlings grown in organic compost was an improved survival rate. RAPD analysis revealed cultivar-dependent somaclonal variation, with the highest polymorphism in the OPK03 marker. The genotype-specific protocol supports efficient large-scale propagation and highlights the need for genetic monitoring in commercial systems.